Determining the household consumption expenditure's resilience towards petrol price, disposable income and exchange rate volatilities - Thomas Habanabakize (Economies, 2021)
One of the core objectives of economic development is to improve people's standards of living. However, both standards of living and consumption expenditures are often determined by disposable income, crude oil prices and exchange rate volatility. The current paper employed quarterly time series data from 2002 to 2020 to analyse the responsiveness of household consumption expenditure to the petrol price, disposable income and exchange rate volatility in South African. The empirical outcome suggested that a long-run relationship exists between variables under consideration. Additionally, the current level of consumption expenditure was found to be determined by income level and exchange rate volatility whilst changes in petrol price had no significant effect on short-term consumption expenditure. Based on these findings, the study suggests that the South African policymakers and government authorities implement policies and strategies that enhance both household income and exchange rate. Those strategies may include strengthening the country's currency, production improvement, inflation rate reduction, and the creation of job opportunities.
Keywords: 330; exchange rate; disposable income; household consumption; oil price; South Africa